2020
DOI: 10.1111/gcb.15218
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term nitrogen loading alleviates phosphorus limitation in terrestrial ecosystems

Abstract: Increased human-derived nitrogen (N) deposition to terrestrial ecosystems has resulted in widespread phosphorus (P) limitation of net primary productivity. However, it remains unclear if and how N-induced P limitation varies over time. Soil extracellular phosphatases catalyze the hydrolysis of P from soil organic matter, an important adaptive mechanism for ecosystems to cope with N-induced P limitation. Here we show, using a meta-analysis of 140 studies and 668 observations worldwide, that N stimulation of soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
96
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 88 publications
(163 reference statements)
8
96
0
1
Order By: Relevance
“…This would allow mineralization of organic P, thus leading to greater acquisition of P by forbs through increasing the availability of P in the rhizosphere. Therefore, long‐term N enrichment may alleviate P limitation in forbs by increasing phosphatase activity (Chen et al., 2020). The greater acidification of the rhizosphere of forbs due to H + exudation would lead to greater P and Mn availability for forbs under N enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…This would allow mineralization of organic P, thus leading to greater acquisition of P by forbs through increasing the availability of P in the rhizosphere. Therefore, long‐term N enrichment may alleviate P limitation in forbs by increasing phosphatase activity (Chen et al., 2020). The greater acidification of the rhizosphere of forbs due to H + exudation would lead to greater P and Mn availability for forbs under N enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 60% of the Amazonian forests grow in highly weathered soils, characterised by very low concentrations of rock-derived P and cations, with evidence for P affecting plant growth (Aragão et al, 2009;Quesada et al, 2010Quesada et al, , 2012. However, even in tropical forests, N availability may be important in controlling key aspects of forest function (Wright et al, 2011;Wright, 2019), and/or greater N availability could help alleviate limitation by other elements (Chen et al, 2020). Therefore, there remain major gaps in our understanding of the role that different elements play in controlling tropical forest function, especially in Amazonia.…”
Section: Introductionmentioning
confidence: 99%
“…While these results indicate that N addition has affected some P pools and fluxes, recent profiling of enzyme activities showed that N addition had no effect on phosphatase activity, whereas both the oxidation of soil organic matter and acquisition of organic N have decreased (Forsmark, 2020). Phosphatase activity may be enhanced by short‐term N addition due to N limitations on enzyme production (Allison et al., 2011), whereas the effect may diminish in the long term (Chen et al., 2020). Accordingly, shifts in P fluxes may have occurred during the initial phases of the N addition treatment, and this P capital may be subsequently conserved in the plant, soil and microbial biomass.…”
Section: Discussionmentioning
confidence: 99%